Detection of homozygous wildtype V1016V using allele-specific polymerase chain reaction in Aedes albopictus - Ahmad Rudi Setiawan; Syananda Zahra Fadila; Teguh Hari Sucipto; Shifa Fauziyah; Safira Madaniyah; Eryantika Cipta Dewi; Sin War Naw; Tukiran Tukiran; Sari Edi Cahyaningrum (Society for Indonesian Biodiversity, 2023)
Abstract. Setiawan AR, Fadila SZ, Sucipto TH, Fauziyah S, Madaniyah S, Dewi EC, Naw SW, Tukiran, Cahyaningrum SE. 2023. Detection of homozygous wildtype V1016V using allele-specific polymerase chain reaction in Aedes albopictus. Biodiversitas 24: 62-67. Aedes sp. is a carrier of several viruses that can infect humans and cause diseases such as zika, yellow fever, chikungunya, and dengue fever. Symptoms of dengue infection vary, consisting of classic dengue fever (DD), dengue hemorrhagic fever (DHF), and dengue shock syndrome. Insecticide spray can be used to manage Aedes mosquitoes chemically. Insecticide substances target nervous system proteins. Voltage-gated sodium channels (VGSC) are rendered inactive by pyrethroid binding. Knockdown is a signal indicating an insect has been knocked down in response to a specific insecticide. However, using insecticides for a long time can cause mosquitoes to become resistant. The pesticide resistance of mosquitoes is known as knockdown resistance (kdr). This study aims to detect kdr mutations (V1016G) in two male Aedes albopictusmosquitos named A1 and A2 collected from settlements in Kranggan, Sawahan, Surabaya, East Java, Indonesia, using allele-specific polymerase chain reaction (AS-PCR) assay. RNA was extracted from the two mosquito samples using an RNA extraction kit. After that, the extracted RNA was tested for kdr mutations using the AS-PCR method. After assaying, both samples are homozygous wildtype (V1016V) because the results showed bands appearing from samples A1 and A2 at 60 bp. On the other hand, this study has the potential to serve as preliminary monitoring for the program controlling vectors.